Tuberculosis latent infection in health care workers: oxidative stress and Quantiferon-TB Plus. (30th September 2020) - Santoro, A; Petrillo, S; Nijhawan, P; Gallo, M G; Brugaletta, R; Gilardi, F; Mastroianni, C; Piemonte, F; Zaffina, S
Abstract: Background: This study moves from recent evidences highlighting: 1) the high sensitivity of Mycobacterium tuberculosis (MT) to perturbation of redox homeostasis induced by oxidative stress; 2) the improvement of Tuberculosis (TB) diagnosis following the introduction of Quantiferon-TB Plus (QFT-Plus) assay. Methods: The QFT-Plus diagnostic performance and the blood antioxidant capacity, expressed as ratio between oxidized (GSSG) and reduced (GSH) forms of glutathione, were determined on three selected populations (40 Health care workers (HCWs) controls, 63 latent TB HCWs, 8 active TB patients). Quantitative Real Time PCR analysis on leukocytes of active TB patients was also performed, in order to identify "redox profiles" of genes mainly involved in the antioxidant response. Results: 1) The glutathione homeostasis was shifted towards an oxidative status in active TB patients respect to controls, as evidenced by the significant decrease of the ratio between free and total GSH, an indirect index of oxidative stress. More reducing conditions were observed in latent TB subjects. 2) The expression profiles of antioxidant genes confirmed the major susceptibility of active TB patients to oxidative stress compared to controls, and highlighted a great individual variability. 3) The diagnostic performance of QFT-Plus test present a moderate concordance with QFT-GIT one, in this preliminary phase. Conclusions: Glutathione has anti-mycobacterial effects in its reduced form GSH, thus the quantification of Free/Total GSH ratio may represent a systemic marker of TB infection and be useful in developing combined therapies. Moreover, the identification of personalized redox profiles will additionally provide an individual antioxidant response to the infection. This project was funded by the Ministry of Health (RF 2016) Key messages: LTBI management represents an objective of primary importance in the field of occupational medicine in order to define a personalized prevention in HCW. A new approach that combines biochemical determinations of redox biomarkers and gene expression in blood will be a novel biomarkers of tuberculosis.